Effectiveness of Anger Management Games on Behavioral and Anger Symptoms of Children with Hyperactivity/Attention Deficit Disorder - Akram Kazemi; Hamidreza Nikyar; Mostafa Najafi (مجله دانشکده پزشکی اصفهان, 2016)
Background: Hyperactivity/attention deficit disorder is the most common neurobehavioral disorders in childhood usually diagnosed before the age of seven. Since anger is a part of the people's life, the children need to learn how to deal with their anger. This project was performed aiming to determine the effectiveness of anger management games on behavioral and anger symptoms of the children with hyperactivity/attention deficit disorder.